Pembuatan Biobriket dari Campuran Tanaman Mendong (Fimbristylis Globulosa) dan Tongkol Jagung dengan Variasi Jenis Perekat - Lusia Valentina Marbun; Erista Adisetya; Mohammad Prasanto Bimantio (Program Studi Teknologi Hasil Pertanian, 2025)
The depletion of fossil fuel reserves necessitates the adoption of renewable alternative energy sources. Bio briquettes derived from agricultural waste biomass, such as Fimbristylis globulosa (mendong) and corn cobs, offer a promising sustainable fuel solution. This study aimed to analyse the effects of raw material composition ratio (mendong and corn cobs) and adhesive type on the characteristics of bio briquettes. The research employed a Complete Randomized Block Design (CRBD) with two factors: (1) Raw material ratio (70% corn cob:30% mendong, 50%:50%, 30%:70%) and (2) Adhesive type (20% concentration: tapioca flour, cornstarch, sago flour). Analyses were conducted on moisture content, ash content, combustion rate, compressive strength, and calorific value. Results indicated that the raw material composition ratio had no significant effect on any tested parameters (compressive strength, moisture content, ash content, combustion rate, or calorific value). In contrast, the variation in adhesive type had a significant effect on all parameters. Thus, this study proved that the type of adhesive is a significant factor affecting the quality of bio briquettes, while the ratio of raw materials in the tested range did not have a significant effect.